2011
DOI: 10.5897/ajpp10.362
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to erythromycin of Campylobacter jejuni and Campylobacter coli isolated from animals and humans

Abstract: The sensititivity of thermophilic Campylobacter strains isolated from caecum of broiler chickens as well as caecum and colon of pigs and human stools, were tested against erythromycin. In 16 strains isolated in broiler chickens, resistance rate was found to be 12.50%. Three of 10 strains of Campylobacter jejuni and one of 6 strains of Campylobacter coli isolated from broiler chickens were resistant to erythromycin. In 15 strains of thermophilic Campylobacters isolated from pigs, resistance rate to erythromycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…However, C. coli isolates were highly susceptible (0% of resistance) to norfloxacin and gentamicin. There are varied literature reports of resistance patterns of C. jejuni and C. coli strains; while some authors established higher resistance among C. jejuni (Tambur et al, 2009), others found higher resistance among C. coli (Jonker and Picard, 2010) and in some studies no difference in resistance were observed among the two species (Uzunovic et al, 2009;Ewnetu and Mihret, 2010). Moreover, no specific reasons have been cited for the differences in resistance among the two species (Luangtongkum et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, C. coli isolates were highly susceptible (0% of resistance) to norfloxacin and gentamicin. There are varied literature reports of resistance patterns of C. jejuni and C. coli strains; while some authors established higher resistance among C. jejuni (Tambur et al, 2009), others found higher resistance among C. coli (Jonker and Picard, 2010) and in some studies no difference in resistance were observed among the two species (Uzunovic et al, 2009;Ewnetu and Mihret, 2010). Moreover, no specific reasons have been cited for the differences in resistance among the two species (Luangtongkum et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter enteritis is usually self-limiting warranting no antimicrobial therapy; but in severe enteritis with complications and in cases of the immune-compromised, antibiotics are necessary in which case the fluoroquinolones and erythromycin are the drugs of choice (Luangtongkum et al, 2009). Moreover increasing resistance among Campylobacter has been reported from different geographical regions to the drugs of choice and other relevant antibiotics used in both human and veterinary medicine (Salihu et al, 2009;Luangtongkum et al, 2009;Tambur et al, 2009). Multidrug-resistant C. jejuni and C. coli have been reported from food animals and retail meats, including poultry (Ge et al, 2003;Gebreyes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At least two types of resistance mechanisms predominate: tetracycline efflux and ribosomal protection (Speer et al 1992). Frequent resistance to tetracyclines was reported from the U.S.A., France and Serbia during the last decade (Avrain et al 2003;Ge et al 2003;Cui et al 2005;Luangtongkum et al 2006;Tambur et al 2010). In 2007, the overall resistance to tetracycline of C. jejuni isolated from poultry meat in the EU was 37%, with the lowest frequency in Denmark (10%) and the highest in France (57%) (EFSA 2010-2).…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter species are motile by means of flagella which are usually single at one or both poles (Barrow and Feltham, 1993;Moolhueijzen et al, 2009). Campylobacteriosis, an important bacteria zoonoses is caused by species from the Genus Campylobacter (Tambur et al, 2013). The Thermophilic species such as Campylobacter jejuni, C. coli, C laris, and C. upsaliensi are the most common causative agents of human diseases (Tambur et al, 2013).…”
Section: Introductionmentioning
confidence: 99%